2022
DOI: 10.32473/jfmca.v69i1.130623
|View full text |Cite
|
Sign up to set email alerts
|

Semi–field Evaluation of Ultra-Low Volume (Ulv) Ground Spray of Aqualuer® 20-20 Against Caged Aedes Albopictus and Non-Target Honey Bee, Apis Mellifera

Abstract: Application of permethrin products by ultra-low volume (ULV) spraying against the container-inhabiting mosquito Aedes albopictus (Skuse) has been used for many years, but the impact of the insecticides on domesticated honey bees, Apis mellifera (Linnaeus) is still lacking. The present study was carried out to evaluate the impact of the permethrin product, Aqualuer® 20-20 (active ingredient: 20.6% permethrin+20.6% Piperonyl butoxide) ULV sprays on caged Ae. albopictus and A. mellifera in open semi-field conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Permethrin toxicity to mosquitoes has been well investigated given its use for the control of adult mosquitoes (Zhang et al 2015 ; Whiten and Peterson 2016 ; Gong et al 2017 ; Sanchez-Arroyo et al 2021 ; 2022 ), but the concentrations affecting the mosquitoes are often reported as nominal. Assumptions about exposures based on dose solution concentrations or possible unintended errors in toxicant delivery to an organism the size of an adult mosquito could lead to inaccuracies in the reported effect concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Permethrin toxicity to mosquitoes has been well investigated given its use for the control of adult mosquitoes (Zhang et al 2015 ; Whiten and Peterson 2016 ; Gong et al 2017 ; Sanchez-Arroyo et al 2021 ; 2022 ), but the concentrations affecting the mosquitoes are often reported as nominal. Assumptions about exposures based on dose solution concentrations or possible unintended errors in toxicant delivery to an organism the size of an adult mosquito could lead to inaccuracies in the reported effect concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Formulated insecticides were used to treat paper or other surfaces to simulate insecticide exposure when they land on treated foliage or other surfaces in the field and LC 50 s (µg/cm 2 ) of mosquito residual adulticides were determined for both species of mosquitoes and the honey bee. In semi-field studies (Sanchez-Arroyo et al 2022a, Sanchez-Arroyo et al 2022b, the differential toxicity of insecticides to Ae. albopictus mosquitoes and honey bees were determined.…”
Section: Introductionmentioning
confidence: 99%